Pedagogical Science in Professional Education - Atamanov Abdukhalil Salomovich (Genius Journals, 2023)
This article discusses the problems of training specialists in vocational education. Pedagogical science in the system of continuous education, increasing its effectiveness, developing the theoretical and methodological foundations of its functioning, forecasting and developing relevant fundamental and applied research, innovative processes in pedagogy, a differentiated form of education, raising the level of scientific research.
Keywords: educational system; educational institutions; pedagogical science; methodological foundations